A new, narrowly endemic species of swamp-dwelling dusky salamander (Plethodontidae: Desmognathus) from the Gulf Coastal Plain of Mississippi and Alabama - Pyron, R. Alexander; O’connell, Kyle A.; Lamb, Jennifer Y.; Beamer, David A. (Zootaxa, 2022)
We describe a new, narrowly endemic species of swamp-dwelling dusky salamander (Plethodontidae: Desmognathus pascagoula sp. nov.) from the Gulf Coastal Plain of southeastern Mississippi and southwestern Alabama based on linear morphometrics, mitochondrial DNA, and single nucleotide polymorphisms from 881 loci produced using genotype-by-sequencing. Some populations of the new species were historically referred to as D. auriculatus, a polyphyletic assemblage of at least three species in the Atlantic and Gulf Coastal Plain from Texas to North Carolina. Populations of D. auriculatus from the Gulf Coastal Plain in Louisiana and Mississippi were recently described as D. valentinei. The new species includes populations that were tentatively referred to D. valentinei, but we find it is morphologically, genetically, and geographically distinct. It is smaller, has a more defined dorsal color pattern, more irregular whitish “portholes” in up to three rows on the lateral surfaces of the body and tail, and a brighter orange or yellowish orange postocular stripe. At present, the new species is known from only six extant populations in the lower Pascagoula, Escatawpa, and Mobile drainages. The latter represents a distinct phylogeographic lineage. We also refer a historical collection from the northeastern side of the Mobile-Tensaw River Delta to this species, suggesting a much broader range in the past. We suspect that more populations remain to be discovered in the area, and their potential species-level distinctiveness should be tested further. This discovery increases knowledge of the biodiversity in the southeastern United States Coastal Plain, a candidate region meeting the global criteria for a “biodiversity hotspot,” and underscores the amount of cryptic diversity likely remaining to be discovered and described in Nearctic salamanders.